CONCERTO app for pediatric inpatients: A qualitative exploration of user experience and empowerment - Hubert Rioux; Helena Bornet dit Vorgeat; Klara M. Posfay-Barbe; Frederic Ehrler; Nadia M. Bajwa (PLoS ONE, 2025)
Introduction Hospitals increasingly use health information technologies such as websites and apps to foster patient engagement. The Geneva University Hospitals developed CONCERTO, an ecosystem of patient applications for this exact purpose. The objectives of this study were 1) to evaluate how pediatric patients and their parents use the app CONCERTO and 2) to pinpoint functionalities that could facilitate patient empowerment and consequently alleviate the stress of children and their parents related to hospitalization. Materials and methods We interviewed 18 children and their parents during their hospitalization at the pediatric unit from May 20th to November 15th, 2022. Firstly, inspired by the Think-Aloud Protocol, we asked participants to complete a few specific tasks using the application. Then, we asked broader questions to better understand how CONCERTO could enhance patient empowerment. We used thematic analysis to explore the rich data set. Results Children and their parents appreciated the features of the app. Specifically, they enjoyed creating an avatar and were grateful to have access to the interactive meal menu and the agenda. Both patients and parents would have appreciated learning about CONCERTO upon their arrival as it could have improved their hospital experience. Participants shared challenges they faced during their hospitalization and made suggestions about how more personalized content in CONCERTO could help overcome negative moments. Conclusions CONCERTO effectively engaged and empowered patients and parents during their hospitalization. Further research is needed to evaluate the overall impact of such an app and understand the hurdles the care team faces in promoting the use of the app.